IEEE 802.11p MAC with spectrum sensing scheme reliable for VANET using the intelligent transportation system. (30th July 2019) - Karthikeyini, S.; Shankar, S.
In congested areas, enough spectrum is needed to transmit safety and non-safety messages. Spectrum Sensing with Distributed TDMA (SSD-TDMA) accesses the channel in a distributed fashion to avoid the collision and the cyclic autocorrelation function is used to detect the energy at the vehicle level for broadcast signal. All information is aggregated for making a decision for data delivery in vehicular environments. The spectrum sensing method is employed to sense broadcast signals for finding out the occupancy status of the spectrum and availability of the licensed frequency bands. The performance of spectrum sensing technique and slot allocation based on the timestamp of a vehicle entering in the RSU coverage area in distributed manner is judged at a congested city state of affairs using the ns2 simulator. The proposed approach SSD-TDMA represents an effective and warranted conversation over Vehicular Adhoc Network (VANET) measured through the reduced delay and overhead of packet constraints.